Culture of human articular chondrocyte in monolayer - Kitadai, Fabio T. (2003)
The purpose of this study was the padronization of the obtained human articular cartilagecell culture methodology. Five patients were selected from Instituto de Ortopedia e Traumatologia do Hospital das Clínicas da Faculdade de Medicina da Universidade de São Paulo (IOT-HC-FMUSP). All patients suffered from anterior ligament lesion with cartilage degeneration. The diagnosis and the surgery were performed by knee arthroscopy. The articular cartilage fragments (weight, 300 to 500 mg) mg were placed in Petri dishes containing Dulbecco´s modified Eagle´s medium (DMEM) with 40µg/ml. The fragment was finely diced and treated with 2mg/ml collagenase in medium DMEM containing 10% fetal serum bovine. The cells isolated were seeded at hight density in T25 flasks in medium DMEM with 10% offetal calf serum (FCS). The cells attached to the flask after 24 hours the cells began to adhere to the flask. By day 3 the cell culture presented elipsoid and star morphology. Cultures fixed and stained with toluidine blue showed extracellular staining, suggesting these cells had begun to synthesize a new matrix. The growth rate of chondrocytes was high in the 2nd and 3nd days of the cultive. The chondrocytes were frozen into liquid nitrogen and showed high viability...